Experimental investigation of the effect of injection pressure on performance and emission of DI Diesel engine fueled with scum oil methyl ester blends - K N, Krishnamurthy; S N, Sridhara (International Journal of Engineering and Technology, 2026)
In the present experimental study dairy wash water was used for the production of scum oil methyl ester as alternate fuel for CI engine which satisfy all the characteristics of the conventional diesel. Dairy waste Scum was converted into bio-diesel by using two stage transesterification processes. First stage acid catalyst esterification process was used in which concentrated H2SO4 was 10 ml, methanol 250 ml, temperature 60°C and reaction time 60 minutes, in second stage base catalyst transesterification process methanol to oil molar ratio of 7.5:1, catalyst concentration of 0.961 wt%, reaction time 49.529 min and temperature 63.46°C was used in which 850 ml of biodiesel was obtained from one liter crude scum oil. Produced Scum oil methyl ester was blend with diesel with various proportions such as [B10, B20, B30, B40 and B100] was analyzed and compared with pure diesel. Prepared test samples were subjected to diesel engine and several tests have been carried out to examine properties, performance, combustion and emission characteristic with varying injection pressure [180, 200 and 220 bar]. Performance and emission characteristic was carried out on diesel engine to determined BSFC, break thermal efficiency and exhaust gas temperature and emission characteristics like CO, CO2, NOx, O2, smoke opacity and HC. The obtained results were compared with diesel and blends of scum oil methyl ester at the three injection pressure. From the overall results obtained for all the blends of diesel and diesel at three operating injection pressure it can be concluded that B20 samples can be used as an alternate fuel at an injection pressure of 200 bar in to CI engine without any modification. This sample will give better performance and less exhaust emission than any other blends. The performance and emission characteristics of B20 samples will remains same as D100.